Identification of Antibacterial Compounds from Endophytic Bacterial Extract of Green Grass Cincau Plant (Premna oblongifolia Merr) - Anna Muthia Soliha; Leny Heliawati; Siti Warnasih (Universitas Pakuan, 2021)
Green grass jelly (Premna oblongifolia Merr) is a plant that belongs to the Verbenaceae family with the Premna genus. The genus Premna has about 200 species in the Verbenaceae family which are spread in tropical to subtropical areas such as Asia, Africa, and Australia. This plant has potential as antibacterial, antipyretic, anti-inflammatory, and antioxidant. This research was conducted to make an extract of endophytic bacteria obtained from green grass jelly plants by maceration method. The extract obtained was tested for its antibacterial activity by disc diffusion method. Extracts with the highest antibacterial activity were identified by FTIR and GCMS. The results showed that the methanol extract of endophytic bacteria of green grass jelly plants had broad spectrum antibacterial activity because it was able to inhibit the growth of Gram-positive bacteria (Bacillus subtilis) and Gram-negative bacteria (Pseudomonas aeruginosa). The results of FTIR and GCMS showed that the active compounds contained in the endophytic bacteria of green grass jelly plants were thought to be Nerolidol compounds or 3,7,11-trimethyl-1,6,10-dokatrien-3-ol which are secondary metabolites of the sesquiterpene alcohol group and play a role in as an antibacterial.